Gap between cognitions and behaviors among children's guardians of influenza vaccination: The role of social influence and vaccine-related knowledge - Jing Wu; Zheng Wei; Yingying Yang; Xiu Sun; Siyi Zhan; Qijing Jiang; Chuanxi Fu (Taylor & Francis Group, 2023)
The seasonal influenza vaccine coverage remains suboptimal among children even though guardians expressed high willingness to vaccinate their children. This study aimed to determine the association between vaccine hesitancy and uptake to facilitate vaccination; thus, bridging the gap. A cross-sectional design, using stratified cluster random sampling, was conducted among guardians of 0-59-month-old Chinese children from July to October in 2019. A structural equation model was applied to explore the interrelationships between factors including vaccine hesitancy, vaccination, social influence, and relative knowledge among guardians. Of the 1,404 guardians, 326 were highly hesitant to vaccinate their children, 33.13% (108/326) of whom had vaccinated their children. Moreover, 517 and 561 guardians had moderate and low vaccine hesitancy, with corresponding vaccine coverage of 42.75% (221/517) and 47.95% (269/516). Guardians' gender, age, and education level were demographic variables with significant moderating effects. Social influence considered impact of communities, family members, friends, neighbors, healthcare workers, bad vaccination experience and sense on price. Actual vaccine uptake was negatively significantly associated with hesitancy (β = -0.11, p < .001) with positive association with social influence (β = 0.61, p < .001). Vaccine hesitancy was negatively significantly associated with relative knowledge (β = -2.14, p < .001) and social influence (β = -1.09, p < .001). A gap is noted between cognitions and behaviors among children's guardians regarding influenza vaccination. A comprehensive strategy including emphasizing benefits of the influenza vaccination, risk of infection, and ensuring high vaccine confidence among healthcare workers can help transform the willingness to engage in the behavior of vaccination.